2010
DOI: 10.1097/nna.0b013e3181e9395e
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' and Nursing Assistants' Reports of Missed Care and Delegation

Abstract: Nurse leaders must focus on implementing strategies to mitigate factors and the consequences of care omissions, including poor patient outcomes. An analysis of point-of-care delivery system failures and ineffective processes is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 19 publications
12
56
0
Order By: Relevance
“…This result is further supported by Standing&Anthony (2008), Berkow et al (2008), and Potter et al (2010), who confirmed that there is a relationship between delegation skills and experience among nurse mangers, suggesting that years of experience results in one improving and growing with practice over time [27]- [4]- [23]. Ruff (2011) and Gravlin & Bittner (2010) confirm a relationship between delegation and education, observing that nursing education is key to ensuring appropriate delegation [25]- [13]. Conversely, Saccomano & Pinto (2011) found that education had no relationship to delegation and that diploma nurses were better prepared to delegate than bachelor degree nurses because they had more years of exposure to real situation of delegation [26].…”
Section: Nurse Mangers Attitude and Demographics Data Relationshipsupporting
confidence: 64%
“…This result is further supported by Standing&Anthony (2008), Berkow et al (2008), and Potter et al (2010), who confirmed that there is a relationship between delegation skills and experience among nurse mangers, suggesting that years of experience results in one improving and growing with practice over time [27]- [4]- [23]. Ruff (2011) and Gravlin & Bittner (2010) confirm a relationship between delegation and education, observing that nursing education is key to ensuring appropriate delegation [25]- [13]. Conversely, Saccomano & Pinto (2011) found that education had no relationship to delegation and that diploma nurses were better prepared to delegate than bachelor degree nurses because they had more years of exposure to real situation of delegation [26].…”
Section: Nurse Mangers Attitude and Demographics Data Relationshipsupporting
confidence: 64%
“…Nurses with little professional experience are often more reluctant to delegate than experienced ones, often maintaining that they lack motivational skills and the ability to supervise. It is said that nurses are willing to take on work that no one else is willing to do, indicating a need for RNs to reprioritise the tasks and work to which they allocate their time and to better identify what should be delegated to others (21)(22)(23).…”
Section: Barriers To Effective Delegationmentioning
confidence: 99%
“…This being said, within the context of overworked staff, due in large part to the chronic nursing shortage and prescribed organizational policies aimed at maximal productivity, the hectic pace of day-to-day nursing care does not lend itself to the fostering of the positive emotions critical for IPC: trust and respect [55]. Yet incongruously, RNs and LPNs are required to display these unfelt emotions towards their colleagues [18].…”
Section: Literature Reviewmentioning
confidence: 99%